2018
DOI: 10.24017/science.2018.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Complement protein and Immunoglobulins Serum levels in Normal Pregnant and Spontaneous Aborted Women

Abstract: Disorder of maternal immune responses during pregnancy triggers immunological rejection of fetus antigens by maternal immune components, contribute to spontaneous abortion or miscarriage. The study was designed to concentrated on immunoglobulins (IgM, IgG and IgA) and complement elements (C3 and C4)   serum levels changes in normal pregnant and abortion women. Study groups were classified into normal pregnant women (20), spontaneous abortion (30) and non-pregnant women (16) as a control group, attending to Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Interestingly, over half of the studied group had at least one abnormal test result for any of the five biomarkers of immunoglobulins or complements. A recent study measured the same five biomarkers, but during the first trimester [15]. To the best of our knowledge, this study is the first published research that evaluated these five biomarkers of immunoglobulin and complements together before pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, over half of the studied group had at least one abnormal test result for any of the five biomarkers of immunoglobulins or complements. A recent study measured the same five biomarkers, but during the first trimester [15]. To the best of our knowledge, this study is the first published research that evaluated these five biomarkers of immunoglobulin and complements together before pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…between the levels of immunoglobulins (specifically IgG and IgM) and abortion. Hiwa et al ( 2018), study discovered notable variations in IgG concentrations between abortion cases and normal pregnancies, but no significant differences were observed in IgM and IgA serum levels across the groups (17). The results of Berger et al's study (2020) showed that in conclusion, combinations of diabetes mellitus (D), obesity (O), and chronic hypertension (H) significantly magnify the risk of preterm birth (PTB), especially provider-initiated PTB (piPTB), and PTB with altered fetal growth or preeclampsia (18).…”
Section: Introductionmentioning
confidence: 96%